Desempenho e análise econômica de frangos de corte alimentados com dietas contendo farelo de acerola em substituição ao milho - Zanetti, Leonardo Henrique [UNESP]; do Polycarpo, Gustavo Valle; Brichi, André Luís Coneglian [UNESP]; Barbieri, Adriano [UNESP]; de Oliveira, Raphael Fortes [UNESP]; Sabbag, Omar Jorge [UNESP]; Cooke, Reinaldo Fernandes; Cruz-Polycarpo, Valquíria Cação [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2014)
It was aimed with this research to evaluate the performance of broiler chickens fed diets containing increasing levels of acerola meal in replacement of corn and analyze the economic viability of that production system. A total of 980 day-old male Cobb chicks were used, allotted in a completely randomized design, with four treatments - inclusion levels (0%, 5%, 10% and 15%) of acerola meal in replacement of corn – and seven replications with 35 birds per experimental unit. The birds were weighed at 21 and 42 days of age to measure the performance data. In the period between 1 and 21 days of age, differences were observed in the feed intake and feed:gain only, in which the inclusion of acerola meal linearly decreased feed intake and improved feed:gain up to a level of 10.25%. For the total rearing period, the control treatment showed higher body weight. The feed:gain showed linear effect, worsening the results with increasing amounts of acerola meal in the diets. In the same period, there was no significant difference in feed intake and productive efficiency index. With regard to the economic analysis, it was found that the lowest final cost per broiler was observed in diets with 10% of acerola meal inclusion in replacement of corn.
Performance and economic analysis of broilers fed diets containing acerola meal in replacement of corn
Keywords: Alternate ingredient; Broiler nutrition; By-products